Comparison of world elite and Japanese elite throwers in the discus throw - Maeda, K.; Ohyama-Byun, K.; Mizushima, J.; Yamamoto, D.; Hirose, K.; Kajitani, R.; Ogata, M. (ISBS Proceedings Archive (Michigan), 2018)
The aim of this study is to clarify the differences between world elite and Japanese elite discus throwers by comparing their hip-shoulder and shoulder-arm separation angles. The performances of 12 male world elite discus throwers (the World group) and 12 male Japanese elite discus throwers (the National group) were analysed. The hip-shoulder and shoulder-arm separation through the throwing motion were greater in the World group than in the National group. Although the shoulder led hip in both the World and National groups, the shoulder led the arm in the National group and the arm led the shoulder in the World group at release. These results showed that the World group released the discus in front of the shoulder while utilising the kinematic-chain appropriately, while the National group released the discus with the arm still trailing behind the shoulder.